Training on the Utilization of Traditional Medicines in the Community of Selayar District (Collaboration with Ksatria Airlangga Floating Hospital) - Purwitasari, Neny; Ekasari, Wiwied; Wahyuni, Tutik Sri; Harianto, Agus; Dahri, Baso; Widyawaruyanti, Aty (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research aims to address the limited knowledge of traditional medicine among communities in Selayar Regency, South Sulawesi. It highlights the significance of improving understanding and usage of traditional medicine to enhance health outcomes in areas with limited healthcare facilities. Method: The study utilized a hybrid approach, involving seminars and training for 50 PKK (Family Welfare Movement) cadres. Pre and post-tests were administered to assess knowledge changes regarding medicinal plants and traditional medicine preparation. Practical Applications: The findings indicate that enhancing the knowledge of PKK cadres can empower them to share this information in their communities, leading to increased use of traditional remedies and improved health outcomes. Conclusion: The study found a notable increase in knowledge, with correct answers rising from 64.54% in the pre-test to 75.67% in the post-test. These results demonstrate the effectiveness of the training and its potential to address health challenges in Selayar Regency through the utilization of traditional medicine.